Sprache – Denken – Wirklichkeit

Alltagspraktiken des Erzählens (Literaturwissenschaft und Linguistik)

Editorial: Alltagspraktiken des Erzählens - Spieß, Constanze; Tophinke, Doris (Literaturwissenschaft und Linguistik)

Sprache – Denken – Wirklichkeit (Basisartikel) - Tophinke, Doris (Praxis Deutsch)

Supporting the Cognitive Process in Annotation Tasks - Seemann, Nina; Geierhos, Michaela; Merten, Marie-Luis; Tophinke, Doris; Wever, Marcel Dominik; Hüllermeier, Eyke (Postersession Computerlinguistik der 40. Jahrestagung der Deutschen Gesellschaft für Sprachwissenschaft)

Inclusive Education and its Actors: Determinants of Social Integration on Students with Emotional and Social Disorders. - Zdoupas, Philippos; Laubenstein, Désirée

Schulentwicklung und Schulleitung – Führung mit Rahmen - Laubenstein, Désirée; Scheer, D.

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Die Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF) – Zentrale Befunde - Wild, Elke; Lütje-Klose, Birgit; Neumann, Phillip; Gorges, Julia (DDS – Die Deutsche Schule)
In der Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF) wurden die psychosoziale und die Leistungsentwicklung bei Kindern mit sonderpädagogischem Förderbedarf im Förderschwerpunkt „Lernen“ von der 3. bis zur 5. Klasse in unterschiedlichen Fördersettings untersucht. Die Ergebnisse quantitativer und qualitativer Zugänge zeigen, dass vor allem proximale Faktoren auf der Ebene der Einzelschule – weniger die Form der Beschulung – für die Entwicklung der Kinder relevant sind.
Keywords: BiLieF; Inklusion; sonderpädagogischer Förderbedarf; Grundschule; Wohlbefinden; Rollenausprägungen sonderpädagogischer Lehrkräfte

Women Phenomenologists on Social Ontology. Vol. 1. Women in the History of Philosophy and Sciences
Part 1: Social Ontology in Edith Stein and Gerda Walther -- Chapter 1. The Role of Empathy in Experiencing Community (Antonio Calcagno) -- Chapter 2. Meaning of Individuals within Communities: Gerda Walther and Edith Stein on the Constitution of Social Communities (Julia Mühl) -- Chapter 3. Edith Stein on Social Ontology and the Constitution of Individual Moral Identity (William Tullius) -- Chapter 4. The Ontic-Ontological Aspects of Social Life. Edith Stein's Approach to the Problem (Anna Jani) -- Chapter 5. Starting from Husserl: Communal Life according to Edith Stein (Alice Togni) -- Chapter 6. The role of the intellectual in the social organism. Edith Stein's analyses between social ontology and philosophical anthropology (Martina Galvani) -- Chapter 7. The Phenomenology of Shared Emotions - Reassessing Gerda Walther (Thomas Szanto) -- Chapter 8. We-Experience - with Walther (Hans-Bernhard Schmid) -- Chapter 9. Gerda Walther between the phenomenology of mystics and the ontology of communities (Anna Piazza:) -- Chapter 10. Do We-Experiences Require an Intentional Object? On the Nature of Reflective Communities (Following Gerda Walther) (Sebastian Luft) -- Part2: The Ontology of Hedwig Conrad-Martius -- Chapter 11. Essence, Abyss, and Self - Hedwig Conrad-Martius on the Non-Spatial Dimensions of Being (Ronny Miron) -- Chapter 12. ``The reinstatement of the phenomenon''. Hedwig Conrad Martius and the meaning of ``being'' (Manuela Massa) -- Chapter 13. From Collectives to Groups - Sartre and Stein on Joint Action and Emotional Sharing (Gerhard Thonhauser) -- Chapter 14. Women as zoa politika, or: Why There Could Never Be a Women's Party. An Arendtian-Inspired Phenomenology of a Female Political Subject (Maria Robaszkiewicz) -- Chapter 15. Ontology is social. How Arendt Solves a Wittgensteinian Problem (Anna-Magdalena Schaupp) This edited volume examines women's voices in phenomenology, many of which had a formative impact on the movement but have be kept relatively silent for many years. It features papers that truly extend the canonical scope of phenomenological research. Readers will discover the rich philosophical output of such scholars as Edith Stein, Hedwig Conrad-Martius, and Gerda Walther. They will also come to see how the phenomenological movement allowed its female proponents to achieve a position in the academic world few women could enjoy at the time. The book explores the intersection of social ontology, phenomenology, and women scholars in phenomenology. The papers offer a fresh look at such topics as the nature of communities, shared values, feelings, and other mental content. In addition, coverage examines the contributions of Jewish women to the science, who were present at the beginning of the phenomenological movement. This remarkable anthology also features a paper on Gerda Walther written by Linda Lopez McAlister, former editor of the feminist journal Hypatia, who had met Walther in 1976. This book features work from the conference ``Women Phenomenologists on Social Ontology,'' held at the University of Paderborn. Overall, it collects profiles and analysis that unveil a hidden history of phenomenology
Keywords: Europe; Central-History; Ontology; Phenomenology; Philosophy; Political science; Political science / Philosophy

Der Frieden mit den Heiden. Die Karolinger, die dänischen Könige und die Seeräuber aus dem Norden - Kamp, Hermann (La productivité d'une crise. Le règne de Louis le Pieux (814-840) et la transformation de l'Empire)

Formen und Funktionen der Burgkapelle im spätmittelalterlichen Herzogtum Burgund: Burgkapellen: Formen - Funktionen - Fragen - Kamp, Hermann (Akten der Internationalen Tagung, Brixen, Bischöfliche Hofburg und Cusanus-Akademie, 2. bis 5. September 2015)

Big Data-Kriege. Über Tötungslisten, Drohnen und die Politik der Datenbanken - Weber, Jutta (Machine Learning – Medien, Infrastrukturen und Technologien der Künstlichen Intelligenz)

Blackbox, Baukasten, Biomarker. Körperkonzepte in der Kontrollgesellschaft - Weber, Jutta (Körper, Materialitäten, Technologien)

Gelingensbedingungen des gemeinsamen Unterrichts an Schwerpunktschulen in Rheinland-Pfalz (GeSchwind). Ausgewählte Forschungsergebnisse - Lindmeier, C.; Laubenstein, Désirée; Guthöhrlein, K. (Empirisch-pädagogische Forschung in inklusiven Zeiten. Konzeptualisierung, Professionalisierung, Systementwicklung)

Inklusion an Schwerpunktschulen in Rheinland-Pfalz - Laubenstein, Désirée; Lindmeier, C. (Inklusive Schul- und Unterrichtsentwicklung. Vom Anspruch zur erfolgreichen Umsetzung.)

Introduction: Autonomous Driving and the Transformation of Car Culture - Weber, Jutta (Degendering the Driver. Sonderausgabe „Transfers: Interdisciplinary Journal of Mobility Studies“ (Hg.: Jutta Weber/Fabian Kröger))

Women Phenomenologists on Social Ontology

Strategies of segregation: race, residence, and the struggle for educational equality - Pöllmann, Andreas (Ethnic and Racial Studies)
Keywords: Sociology and Political Science; Anthropology; Cultural Studies

La formación intercultural de los futuros maestros mexicanos de secundaria - Pöllmann, Andreas (Revista Electrónica de Investigación Educativa)
La provisión de oportunidades para el aprendizaje intercultural a través del contacto con “lo extranjero” es fundamental para el bienestar cultural, social y económico de los países multiculturales. El contexto mexicano es de particular interés tanto por su extraordinaria diversidad sociocultural como por sus niveles epidémicos de analfabetismo intercultural. Con base en una encuesta realizada a 189 estudiantes de la Escuela Normal Superior de México, el presente artículo explora (i) la importancia percibida del contacto con “lo extranjero” como parte de la formación magisterial, (ii) el interés existente por la participación en algún programa de intercambio internacional y (iii) el nivel de experiencias concretas con “lo extranjero”. A partir de una serie de estadísticas descriptivas –que demuestran las percepciones, intereses y experiencias de los futuros maestros de secundaria– se manifiesta la importancia de un mayor compromiso institucional y gubernamental con la formación intercultural del magisterio normalista.
Keywords: Education